PENINGKATAN HASIL BELAJAR PESERTA DIDIK SMP PADA MATERI PERSAMAAN LINEAR SATU VARIABEL DENGAN MODEL DISCOVERY LEARNING - Winda Nursawitri; Devi Nurul Yuspriyati; Marchasan Lexbin Elvi Judah Riajanto; Gida Kadarisma; Aditya Kresnawan (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2023)
This research is a Classroom Action Research (CAR) which aims to improve student learning outcomes after using the discovery learning model. The subjects of this class action research were 22 students of class VII. Data collection techniques were carried out by means of observation, documentation and also using test questions. The increase in student learning outcomes will be seen based on the value of students in working on individual questions that will be given before and after the delivery of the material. Based on the results of the study, it showed that a) In the initial conditions, the students' test results were 13.64% with an average score of 26.55. b) In the first cycle, student learning outcomes increased to 36.36% with an average value of 55.77 c) Student learning outcomes in the second cycle increased to 72.73% with an average score of 73.14 d) Most of the students' learning outcomes have met the KKM. From the results of this study it can be concluded that there is an increase in student learning outcomes using the discovery learning model.